2020
DOI: 10.1136/bmjopen-2019-035113
|View full text |Cite
|
Sign up to set email alerts
|

Lubricant Investigation in Men to Inhibit Transmission of HPV Infection (LIMIT-HPV): design and methods for a randomised controlled trial

Abstract: IntroductionGay, bisexual and other men who have sex with men (gbMSM) have an increased risk of human papillomavirus (HPV) infection and HPV-associated diseases, such as anal cancer and anogenital warts. A carrageenan-based lubricant could prevent HPV infection, thereby reducing the disease burden in this population. This paper describes the protocol for the Lubricant Investigation in Men to Inhibit Transmission of HPV Infection (LIMIT-HPV) study, an ongoing randomised controlled trial (RCT), evaluating effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Although samples from participants in the placebo arm were not inhibited in Experiment #3, in concentrated samples the internal control was not amplified in 3% of samples in the placebo arm, suggesting the presence of other inhibitors. For ongoing or recently completed studies evaluating carrageenan, 2,11–13 the current results provide reassurance that carrageenan infrequently inhibits the amplification of DNA, and carrageenan does not impede HPV DNA extraction.…”
Section: Discussionmentioning
confidence: 56%
“…Although samples from participants in the placebo arm were not inhibited in Experiment #3, in concentrated samples the internal control was not amplified in 3% of samples in the placebo arm, suggesting the presence of other inhibitors. For ongoing or recently completed studies evaluating carrageenan, 2,11–13 the current results provide reassurance that carrageenan infrequently inhibits the amplification of DNA, and carrageenan does not impede HPV DNA extraction.…”
Section: Discussionmentioning
confidence: 56%
“…26 The 3 protocols were also from North America. [27][28][29] For studies in humans, the sample size ranged from 13 to 348 for published studies 16,24 and from 13 to 380 for protocols. 27,28 Of the 16 in vitro (Table 1) and in vivo studies (Table 2), the majority used pseudovirion (PsV) as the source of HPV, 9,10,[12][13][14][15][16][17][18]20,22,23 whereas other studies used bovine papillomavirus type 1 (BPV1), 8 furin-cleaved PsV (fcPsV), 19 or virus-like particle (VLP) 21 in addition to PsV.…”
Section: Resultsmentioning
confidence: 99%
“…Results from ongoing or recently completed studies evaluating carrageenan could potentially provide more evidence for (or against) carrageenan's potential as a preventive agent against HPV. 25,[27][28][29] These ongoing or recently completed studies that tested carrageenan alone or carrageenan-combination products are discussed hereinafter.…”
Section: Ongoing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the CATCH clinical trials showed a 36% reduction in newly acquired HPV infection in women who had applied carrageenan-containing gels ( 67 ). However, there have been safety concerns and absence of protective effects with carrageenan against anal HPV infections ( 39 , 68 ). Another carrageenan study (ClinicalTrials registration no.…”
Section: Discussionmentioning
confidence: 99%